3 Evaluation of HO-1 involvement in melanoma resistance to BRAF inhibitor vemurafenib. (1st December 2018) - Loi, Giulia; Furfaro, AnnaLisa; Adelaide Pronzato, Maria; Pietra, Gabriella; Nitti, Mariapaola
Abstract: Introduction: The point mutation of the BRAF gene (BRAFV600E) is present in more than 50% of melanoma. This mutation determinate the continuous activation of MAPK pathway, which favours cell survival and proliferation. Vemurafenib/PLX4032 (PLX4032) is an inhibitor of BRAFV600 used for the therapy of these tumours, but, after an initial positive response, in many cases a relapse of the disease occurs. HO-1 is the inducible form of heme oxygenase and overexpression is involved in the growth and resistance to therapy of different types of tumours. In this study we have evaluated the involvement of HO-1 in chemoresistance and angiogenesis of BRAFV600E primary melanoma cells. Materials and methods: We used a primary melanoma cell line, derived from a metastasis from a patient, and exposed cells to PLX4032 (1–10 µM). The role of HO-1 was studied by gene silencing or using the pharmacological inhibitor of HO-1 tin-mesoporphyrin IX (SnMP-IX), a drug used to treat hyperbilirubinemia. Angiogenic potential was evaluated by using bovine aortic endothelial cells (BAEC) isolated in our laboratory. Results: Primary melanoma cells (MeOV-1) were exposed to 1–10 µM PLX4032 for 24 hour. MTT and Trypan blue assays showed a reduction in cell viability of 45% and immunoblot and qRTPCR analyses revealed a significant upregulation of HO-1 expression. HO-1 silencing or exposure to 10 µM SnMP-IX further decreased cell viability after exposure to PLX4032. Subsequently, we evaluated the angiogenetic potential of melanoma cells. Medium derived from MeOV-1 cells, exposed to 10 microlar PLX4032, was used to treat BAEC seeded on Matrigel. Tube formation, branching and density were increased in comparison to BAEC exposed to the medium from untreated MeOV-1 cells. Interestingly, when BAEC were treated with conditioned medium from MeOV-1 cells and HO-1 was silenced, 10 µM PLX4032 showed a reduced ability to form tubes. Conclusions: These Results highlight an important role of HO-1 in favouring melanoma resistance to target therapy and angiogenesis. Supported by the University of Genoa, Department of Experimental Medicine.